Molecular phylogeny of the Ellobiidae (Gastropoda: Panpulmonata) supports independent terrestrial invasions - Romero P.E. (2016)
This work was supported by the German funding program “LOEWE − Landes-Offensive zur Entwicklung Wissenschaftlich-ökonomischer Exzellenz” of the Hesse’s Ministry of Higher Education, Research and the Arts, and by JSPS KAKENHI (No. 26291077). P.R. also received a PhD scholarship from CONCYTEC - Peru. We would like to thank Benôit Dayrat, Antonio de Frias Martins, Adrienne Jochum and Alexander Weigand for providing samples or suggestions for this work, and to Claudia Nesselhauf for her support in the laboratory. We also thank the editor and reviewers for their comments on the manuscript. This is Contribution #234, Bermuda Biodiversity Project (BBP), Bermuda Aquarium, Natural History Museum and Zoo, Department of Conservation Services.